Usefulness of Whole-Body Fluorine-18-Fluorodeoxyglucose Positron Emission Tomography in Patients with Neurofibromatosis Type 1: A Systematic Review - Giorgio Treglia; Silvia Taralli; Francesco Bertagna; Marco Salsano; Barbara Muoio; Pierluigi Novellis; Maria Letizia Vita; Fabio Maggi; Alessandro Giordano (Radiology Research and Practice)
Aim. To systematically review the role of positron emission tomography (PET) with fluorine-18-fluorodeoxyglucose (FDG) in patients with neurofibromatosis type 1 (NF1). Methods. A comprehensive literature search of published studies regarding FDG-PET and PET/CT in patients with NF1 was performed. No beginning date limit and language restriction were used; the search was updated until December 2011. Only those studies or subsets in studies including whole-body FDG-PET or PET/CT scans performed in patients with NF1 were included. Results. We identified 12 studies including 352 NF1 patients. Qualitative evaluation was performed in about half of the studies and semiquantitative analysis, mainly based on different values of SUV cutoff, in the others. Most of the studies evaluated the role of FDG-PET for differentiating benign from malignant peripheral nerve sheath tumors (MPNSTs). Malignant lesions were detected with a sensitivity ranging between 100% and 89%, but with lower specificity, ranging between 100% and 72%. Moreover, FDG-PET seems to be an important imaging modality for predicting the progression to MPNST and the outcome in patients with MPNST. Two studies evaluated the role of FDG-PET in pediatric patients with NF1. Conclusions. FDG-PET and PET/CT are useful methods to identify malignant change in neurogenic tumors in NF1 and to discriminate malignant from benign neurogenic lesions.